A STUDY ON THE IMPACT OF COFFEE LELET JHON SERVICE QUALITY ON CUSTOMER - Hendri Wibowo; Widiyanti Cahyani; Endah Subekti; Ahmad Arif Darmawan (CV. Radja Publika, 2024)
A representative food service sector that frequently meets fundamental human requirements is coffee. The younger generation consumes more than the middle and older generations combined among consumers. They base their decision to buy from the coffee shop on its distinctiveness and distinctive features, such as its upscale interior, premium drinks, selective marketing, and varied menus. Coffee shops provide simple meals, a place to study, a place to work, and a comfy place to rest, among other things. This study conducted an empirical investigation of the variables influencing coffee customers' purchase decisions. The method of this study is descriptive qualitative and uses primary and secondary as the data. Then, the purposive sampling techniq used to determine sampling of location and participans, which number of seventy five participants. The data analyzed used IPA ( Importance Performance Analysis ) and CSI ( Customer Satisfaction Indeks ). The analysis showed that the IPA matrix or known as product quality was in quadrants I and quadrants II. While CSI result is 72%, could be concluded that customer are satisfied about product and service in Lelet Coffee Shop John Lasem. Lelet Coffe Shop John Lasem is espected to make continuous improvements to quality atributtes off cofffee drinks as with customer expectations.